Art Asset Management in Traditional Arts Organizations: A Case Study of Sanggar Cahaya Art, Denpasar, Bali - Lanus, I Ketut; Hartono; Purnomo, Sucipto Hadi (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2025)
Art empowers to see artists, art, and society as assets that encourage critical thinking, feeling, and rereading the problems. Artists, art, and society are art assets that have not been understood as important aspects that are interrelated, especially in traditional art organizations. This paper seeks to strengthen art assets as a way to obtain holistic and sustainable art management in traditional art organizations. Data were collected using in-depth observations of the management of art assets in the studio. In-depth interviews were conducted to collect primary data from sources who understand both in terms of knowledge and are actors in the art space. In addition, the data was confirmed and strengthened using previous studies. The results show that there is an art studio institution in the form of an art studio that presents art activities in the form of training, creation of works of art, and performances of traditional art. In addition, in this traditional art institution there is active public (community) involvement in the art space.